2021
DOI: 10.3390/plants10081543
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Area of Collection Determines the Chemical Composition and Antimicrobial Potential of Three Extracts of Chilean Propolis

Abstract: The biological properties of chilean propolis have been described and include antibacterial, antifungal and antibiofilm activities. Propolis has a strong antimicrobial potential. Clinical experiences with synthetic antibiotics indicated the need to discover new sources of bioactive compounds associated with ethnopharmacological knowledge or natural sources such as propolis. The microscopic analysis of pollen grains from plants allows us to determine the botanical origin of the propolis samples. In Angol, sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…Globally, the presence of these compounds (phenolic acids and flavonoids) in propolis samples is characteristic of poplar buds [ 41 , 87 , 87 ]. This agrees with the analysis of the pollen, which showed that the pollen of the species Populus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, the presence of these compounds (phenolic acids and flavonoids) in propolis samples is characteristic of poplar buds [ 41 , 87 , 87 ]. This agrees with the analysis of the pollen, which showed that the pollen of the species Populus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Los polifenoles presentes en la miel de ulmo y los taninos, compuestos que han sido cuantificados también en propóleos han permitido estudiar la capacidad ciatrizante de los productos apícolas.En el caso de algunas muestras de propóleos chilenos presentaron elevado contenido de compuestos fenólicos donde se identificaron flavonoides, antocianidinas, taninos y otros tipos de moléculas (9).…”
Section: Desarrollounclassified
“…Its extensive use within bacteriology, virology, parasitology, and even mycology lists it as promising [67]. Propolis has a promising antimicrobial effect on gram‐positive bacteria [24], as well as gram‐negative bacteria [32]. Table 4 shows the potential of propolis on microorganisms such as bacteria, fungi, and parasites through in vitro assays.…”
Section: Antimicrobial Activitymentioning
confidence: 99%